Contrasting long-term population trends of beach-nesting shorebirds under shared environmental pressures. (August 2021) - Kwon, Eunbi; Robinson, Samantha; Weithman, Chelsea E.; Catlin, Daniel H.; Karpanty, Sarah M.; Altman, Jon; Simons, Theodore R.; Fraser, James D.
Abstract: Identifying the drivers of long-term population change is a key goal of ecological studies. It is complicated by extrinsic and intrinsic factors that may covary with time and/or operate on a time lag. For migratory shorebirds that breed on the barrier islands of eastern North America, populations may be limited by the anthropogenic, climatic, biological environments they encounter throughout the annual cycle. Using three-decades (1989–2017) of breeding monitoring data collected by the National Park Service at two national seashores in North Carolina (Hatteras and Lookout), we examined the potential drivers of nesting piping plover ( Charadrius melodus ) and American oystercatcher ( Haematopus palliates ) populations. Hatteras had five times more annual visitors than Lookout, and our modelling revealed a strong negative relationship between the population size of breeding plovers and human activity and a positive relationship with protection efforts aimed at reducing disturbance. Breeding and wintering climatic conditions, population productivity, and nesting habitat availability showed only weak effects. Thus, a decade-long decline in plover numbers at both seashores starting in the mid-90s reversed as the parks' visitor counts decreased and stricter protections from potential disturbance were implemented. However, the two sympatric populations of oystercatchers showed the opposite population trends from each other at the neighboring seashores, increasing only on Lookout after a hurricane improved habitat and subsequently the reproductive output. Our study suggests a strong relationship between the anthropogenic environment and the population trend of a threatened species and, simultaneously, the important role of stochastic events in shaping populations of long-lived shorebird species.